SOEP-IS 2016 - PBRUTTO: Person-related gross file - DIW Berlin / SOEP (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
The pbrutto dataset contains person-related information (of the gross sample) which is not asked in the person questionnaire but is instead generated by the interviewers during fieldwork.
Keywords: 330